A new scaly ommatine beetle (Coleoptera: Archostemata) from mid-Cretaceous Kachin amber. (July 2022) - Song, Zhenyu; Jarzembowski, Edmund A.; Xiao, Chuantao
Abstract: A rare archostematan beetle, Lepidomma beuteli sp. nov. (Insecta: Coleoptera: Archostemata), is described based on a well-preserved specimen from mid-Cretaceous Kachin amber. It is the fourth species of the genus from the same locality that can be distinguished from the other three congeners by its elongated scape, exposed neck and, especially, ridged pronotum. The new species was probably adapted to a surficial, arboreal, diurnal lifestyle from its external appearance. The specialization of scaly elytra also helps to reveal the importance of scale development in mid-Cretaceous Kachin beetles.